Telemedicine for Epilepsy Support in Resource-Poor Settings - Patterson, Victor (Frontiers in Public Health, 2014)
The Problem Epilepsy is a common disease worldwide causing significant physical and social. disability. It is one of the most treatable neurological diseases. Yet in rural, poorer countries like much of India and Nepal most people with epilepsy are not on any treatment often because they cannot access doctors. Conventional Approaches It is being appreciated that perhaps doctors are not the solution and that enabling health workers to treat epilepsy may be better. Few details however have been put forward about how that might be achieved. Thinking differently Untreated epilepsy should be considered a public health problem like HIV/AIDS, the various steps needed for treatment identified and solutions found. Telemedicine Approaches Telemedicine might contribute to two steps - diagnosis and review. A tool which enables non-doctors to diagnose episodes as epileptic has been developed as a mobile phone app and has good applicability, sensitivity and specificity for the diagnosis. There are a number of ways in which the use of phone review or SMS can improve management. Conclusions Telemedicine, as part of a public health program, can potentially help the millions of people in the resource-poor world with untreated epilepsy.